Anatomic Acromioclavicular Joint Reconstruction with and without Acromioclavicular Ligament Reconstruction: A Comparative Biomechanical Study. (April 2023) - Johnson, Steven M; Esquivel, Amanda O; Lovse, Lisa; Cracchiolo, Allison M; Bishai, Shariff K; Chen, Chaoyang; Lemos, Stephen E
Background: The purpose of this study was to determine if adding a reconstructed superior acromioclavicular (AC) joint ligament adds significant biomechanical stability to the AC joint over anatomic coracoclavicular (CC) ligament reconstruction alone. Methods: Fourteen cadaver shoulders were used for the comparison of biomechanical stability among the anatomic CC ligament reconstruction alone, CC and AC ligament reconstruction, and the intact groups by measuring the displacement under cyclic loads. A load to failure test was then performed in the vertical direction at a loading rate of 2 mm /sec to determine surgical-repair joints' tolerance to the maximum failure load. Results: The average peak-to-peak displacement induced by cyclic load in the sagittal axis and vertical axis direction was not significantly different between CC ligament reconstruction, CC and AC ligament reconstruction, and intact groups. The maximum failure load for the CC reconstruction (224.9 ± 91.8 N (Mean ± SEM)) was lower than CC/AC reconstruction groups (326.2 ± 123.3 N). The CC/AC reconstruction group failed at a significantly higher load (t test, p = 0.016) than the CC reconstruction group. Conclusion: CC/AC reconstruction surgical technique yielded a better shoulder stability than CC ligament alone reconstruction that may better maintain reduction of the AC joint. Level of Evidence: Level II .